Valuasi Ekonomi Taman Wisata Alam Gunung Pancar Kabupaten Bogor - Sukwika, Tatan; Kasih, Hendrietta (JURNAL DESTINASI PARIWISATA, 2020)
Mount Pancar Nature Park (TWAGP) was located in Karang Tengah Village, Babakan Madang District, Bogor Regency. As a unity of sustainability, the TWAGP ecosystem must be able to provide benefits with various values. In the context of the valuation approach, of course, there are practical and normative dimensions for selecting ecosystem services. This study aimed to determine the factors that affect the number of visits to TWAGP and calculate the economic valuation of TWAGP based on the travel cost method (TCM). The method used was TCM. This method was calculated based on total consumer surplus, the coefficient of travel expenses, and total visits respondents. The analysis showed that four factors influence visit frequency, to TWAGP including, cost of travel, level of education, length of knowledge and distance travelled. The consumer surplus of individuals per visit was Rp209.000, and the total economic value was Rp8.535.978.000. The recommendation is a response to the willingness of visitors to pay an additional entry fee than what enforced needs to followed by improving the quality of tourist attractions so that visitors are satisfied and increasingly want to return to visit.   Keyword : Consumer surplus, Economic valuation, Mount pancar nature park, Sustainability, Travel cost method